2015
DOI: 10.1016/j.semcancer.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of the tumor microenvironment: Stromal cells and vessels

Abstract: Lymphomas develop and progress in a specialized tissue microenvironment such as bone marrow as well as secondary lymphoid organs such as lymph node and spleen. The lymphoma microenvironment is characterized by a heterogeneous population of stromal cells, including fibroblastic reticular cells, nurse-like cells, mesenchymal stem cells, follicular dendritic cells, and inflammatory cells such as macrophages, T- and B-cells. These cell populations interact with the lymphoma cells to promote lymphoma growth, surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 126 publications
0
38
0
2
Order By: Relevance
“…15,16,43 Here, we provide evidence for the presence of noncanonical GLI1 transcriptional activation mediated by IKKb. Using in vitro stromal systems and in vivo models of DLBCL, we found that inhibiting IKKb-mediated NF-kB activation and GLI1 synergistically decreased DLBCL cell viability, supporting a novel therapeutic approach for DLBCL based on concomitant inhibition of NF-kB and GLI1.…”
Section: Discussionmentioning
confidence: 59%
“…15,16,43 Here, we provide evidence for the presence of noncanonical GLI1 transcriptional activation mediated by IKKb. Using in vitro stromal systems and in vivo models of DLBCL, we found that inhibiting IKKb-mediated NF-kB activation and GLI1 synergistically decreased DLBCL cell viability, supporting a novel therapeutic approach for DLBCL based on concomitant inhibition of NF-kB and GLI1.…”
Section: Discussionmentioning
confidence: 59%
“…4 and 5) is thus a result of neutralization of heparanase contributed by the tumor microenvironment. The microenvironment of B-cell lymphomas contains variable numbers of immune cells (i.e., T-cells, macrophages, neutrophils), stromal cells (i.e., fibroblasts), and endothelial cells (17,32,33), many of which have been reported to express heparanase (34,35). The significance of the tumor microenvironment in tumorigenesis is well documented and accepted (36).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the tumor microenvironment in tumorigenesis is well documented and accepted (36). In B lymphomas, a complex cross-talk between the lymphoma cells and their respective microenvironment is bidirectional, and multiple secreted factors and cell surface molecules contribute to the activation of signaling pathways in both the lymphoma and stromal cells (32), many of which are targets for the development of lymphoma therapeutics (37). Heparanase activity is thought to release a multitude of HS-bound cytokines, chemokines, and growth-promoting factors sequestered in the ECM and convert them into bioavailable and biologically active mediators that promote cell proliferation, survival, and motility (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study revealed that chemokines and adhesion molecules, which are components of the tumor microenvironment, contribute to the migration and homing of malignant B lymphocytes (19); these molecules include L-selectin, C-X-C chemokine receptor type 4, lymphocyte function-associated antigen 1, C-C chemokine receptor type (CCR)7 and CCR2 (19). Additionally, the microenvironment is crucial for the survival of malignant T and B lymphocytes (27). In recent years, the interaction between the tumor microenvironment and MSCs, and the functions in tumor growth and progression, have been identified (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the interaction between cancer cells and the stromal cells of the tumor microenvironment is required for the survival and localization of cancer cells (27)(28)(29). Recently, targeted treatments based on cytokines and adhesion molecules have been investigated, leading to improvements in the treatment of tumors and inhibition of tumor metastasis (30).…”
Section: Discussionmentioning
confidence: 99%